How Do Couples Cope With Unemployment: Examining Relationships Among Support, Undermining, and Depression. (July 2019) - Schauss, Eraina; Howell, Kathryn; Ellmo, Frances
The purpose of this study was to examine dyadic coping constructs of support and undermining and their relationship with depressive symptoms among couples experiencing unemployment. A 1-year longitudinal correlational field study employing cross-lag autoregressive models among 417 job seekers and their partners was conducted. Results highlighted the significance of full-time reemployment status as the strongest predictor of changes in depressive symptoms over time. Specifically, depressive symptoms declined for those achieving full-time reemployment. Results of χ 2 difference tests indicated no difference in the effects of support and undermining on depression. Furthermore, no gender differences were found between male and female coping processes and depressive symptoms. Implications for clinical interventions and future research directions are discussed.